Effect of Plectranthus amboinicus Leaf Extract on the Quality Attributes of Microencapsulated Fish Oil Fortified Soup Powder - Lekshmi, R. G. K.; Jayathilakan, K.; Sarika, K.; Priya, E. R.; Greeshma, S. S.; Sultana, Khudsia; Tejpal, C. S.; Mathew, Suseela (Fishery Technology, 2019)
The effect of Plectranthus amboinicus leaf extract (PAE) (phenolic content of 2559.56 mg gallic acid equivalents/L) addition in a microencapsulated fish oil fortified soup powder was evaluated in the present study. Fortification of PAE significantly improved the color, rehydration and water activity of the soup powder. The oxidative indices unveiled the role of PEA in protecting the MFO fortified soup powder from oxidative deterioration during the storage period. No faecal coliforms, yeast and mould growth was observed in MFO and PAE fortified soup powder whereas mould growth was there in the control samples. The fortified soup powder has scored high in terms of aroma, taste, consistency and overall acceptability proving its sensory acceptance. The significant findings of the storage study clearly depicted the antioxidant, antibacterial, antifungal as well as flavour enhancing potential of PAE and hence it can be recommended as a potent natural preservative for fish oil incorporated food systems.